2016
DOI: 10.1016/j.physletb.2016.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Updated constraints on spatial variations of the fine-structure constant

Abstract: Recent work by Webb et al. has provided indications of spatial variations of the fine-structure constant, α, at a level of a few parts per million. Using a dataset of 293 archival measurements, they further show that a dipole provides a statistically good fit to the data, a result subsequently confirmed by other authors. Here we show that a more recent dataset of dedicated measurements further constrains these variations: although there are only 10 such measurements, their uncertainties are considerably smalle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 19 publications
1
37
0
Order By: Relevance
“…Other analyses have confirmed these results [3,4], although the inclusion of more recent measurements reduces the allowed amplitude by about twenty percent [5], to a maximum of about 8 parts per million (with no significant changes to the preferred direction). Although it is clear that some systematic effects are present in the archival data [6], it is presently unclear if they could explain the above results [7,8].…”
Section: Introductionmentioning
confidence: 71%
“…Other analyses have confirmed these results [3,4], although the inclusion of more recent measurements reduces the allowed amplitude by about twenty percent [5], to a maximum of about 8 parts per million (with no significant changes to the preferred direction). Although it is clear that some systematic effects are present in the archival data [6], it is presently unclear if they could explain the above results [7,8].…”
Section: Introductionmentioning
confidence: 71%
“…Convert d L and σ d L to μ and σ μ using Eqs. (14) and (15). Calculate the anisotropic distance modulus μ using Eq.…”
Section: Simulation From Advanced Ligo and Virgomentioning
confidence: 99%
“…However, a e-mail: linhn@ihep.ac.cn b e-mail: cqujinli1983@cqu.edu.cn c e-mail: lixin1981@cqu.edu.cn some other observations show that the universe may deviate from the statistical anisotropy. These include but not limited to the large scale bulk flow [8,9], the CMB temperature anisotropy [10,11], the spatial variation of the electromagnetic fine-structure constant [12][13][14][15], the anisotropy of the distance-redshift relation of type-Ia supernovae [16][17][18]. If the universe is indeed anisotropic, it implies that there are new physics beyond the standard model.…”
Section: Introductionmentioning
confidence: 99%
“…[8], and the rest 10 measurements are taken from various literatures and are compiled in Ref. [9]. We find the dipole direction pointing Ω m0 = 0.278, which are derived by fitting to the Union2.1 data set [34] using the standard ΛCDM model.…”
Section: Observational Constraintsmentioning
confidence: 99%
“…22 −0.20 ) × 10 −5 [7]. Recently, Pinho & Martins [9] carried out a joint analysis of a larger number of old α e data [8] and ten more recent measurements of α e [10][11][12][13][14][15][16][17], and found that the dipolar variation of α e with amplitude (0.81±0.17)×10 −5 is still a good fit to the combined data set, while the statistical uncertainty is significantly reduced compared with previous results.…”
Section: Introductionmentioning
confidence: 99%